2003
DOI: 10.1002/bjs.4034
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of prognostic factors in rectal cancer using high-resolution magnetic resonance imaging

Abstract: High-resolution MRI of the rectum allows preoperative identification of important surgical and pathological prognostic risk factors. This may allow both better selection and assessment of patients undergoing preoperative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
425
5
22

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(473 citation statements)
references
References 23 publications
14
425
5
22
Order By: Relevance
“…This correlation was reported by Brown et al (2003) in a single-centre experience and has been described by other centres (Blomqvist et al, 1999;BeetsTan et al, 2001;Bissett et al, 2001;Botterill et al, 2001). A large international prospective multicentre study (MERCURY trial) has demonstrated that the extent of tumour seen on the preoperative MRI scan is equivalent to that seen in the resected pathological specimen in patients who undergo initial surgery with or without short-course preoperative radiotherapy (MERCURY Study Group, 2006).…”
supporting
confidence: 53%
“…This correlation was reported by Brown et al (2003) in a single-centre experience and has been described by other centres (Blomqvist et al, 1999;BeetsTan et al, 2001;Bissett et al, 2001;Botterill et al, 2001). A large international prospective multicentre study (MERCURY trial) has demonstrated that the extent of tumour seen on the preoperative MRI scan is equivalent to that seen in the resected pathological specimen in patients who undergo initial surgery with or without short-course preoperative radiotherapy (MERCURY Study Group, 2006).…”
supporting
confidence: 53%
“…In nonirradiated patients, tumor involvement of the resection margin could be predicted or excluded with a high reliability (PPV 80% and NPV 89%). These results are not in agreement with those reported in a recent review by Dent et al (5), who found a generally low PPV, ranging from 20% to 80%, except for a PPV of 89% reported by Brown et al (9). Because our results showed a significant negative influence of chemoradiation on the reliability of MRI in assessing the mrMF status (PPV reduced to 42 %), caution should be exercised when discussing previous studies that included irradiated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, many of the previous investigations included irradiated patients (6)(7)(8)(9)(10)(11)(12) and it is known that the value of MRI restaging after chemoradiation is reduced, because of posttherapeutic inflammation and fibrosis (13)(14)(15)(16). To our knowledge, the impact of chemoradiation on the reliability of MRI in assessing tumor involvement of the mesorectal fascia has not been analyzed previously in a comparative study.…”
mentioning
confidence: 99%
“…An advantage of MRI is the ability to delineate the tumour and its relationship to the mesorectal fascia. High-resolution MRI predicted mesorectal fascia involvement with 92% agreement [14]. According to the results of the prospective MECURY trial, high-resolution MRI has sensitivity of 94% and specificity of 92% for predicting negative circumferential margins (CRM) after surgery [15].…”
Section: Tumour Diagnosis and Stagingmentioning
confidence: 99%
“…After dividing the inferior mesenteric vein under the pancreas and the inferior mesenteric artery (IMA), complete mobilization is achieved by lateral dissection and mobilization of the splenic flexure and the descending colon and freeing the greater omentum from the transverse colon. Dissection will proceed with medial dissection of distal sigmoid and rectum [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%